2021
DOI: 10.1123/jmpb.2021-0021
|View full text |Cite
|
Sign up to set email alerts
|

Implications and Recommendations for Equivalence Testing in Measures of Movement Behaviors: A Scoping Review

Abstract: Equivalence testing may provide complementary information to more frequently used statistical procedures because it determines whether physical behavior outcomes are statistically equivalent to criterion measures. A caveat of this procedure is the predetermined selection of upper and lower bounds of acceptable error around a specified zone of equivalence. With no clear guidelines available to assist researchers, these equivalence zones are arbitrarily selected. A scoping review of articles implementing equival… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…Consistent with some guidelines ( 1 , 4 ), we encourage that equivalence testing be conducted and that the equivalence zone required for the two measures to be deemed statistically equivalent reported. This avoids the use of arbitrary a priori thresholds (e.g., ±10% or ±20%) that produce dichotomous outcomes that are sensitive to minor deviations in threshold selection ( 14 ). Specifically, a review on the topic demonstrated that a 5% change in threshold selection altered the conclusions of 75% and 71% of validation studies in children/youth and adults, respectively ( 14 ).…”
Section: How To Interpret Validation Study Results?mentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with some guidelines ( 1 , 4 ), we encourage that equivalence testing be conducted and that the equivalence zone required for the two measures to be deemed statistically equivalent reported. This avoids the use of arbitrary a priori thresholds (e.g., ±10% or ±20%) that produce dichotomous outcomes that are sensitive to minor deviations in threshold selection ( 14 ). Specifically, a review on the topic demonstrated that a 5% change in threshold selection altered the conclusions of 75% and 71% of validation studies in children/youth and adults, respectively ( 14 ).…”
Section: How To Interpret Validation Study Results?mentioning
confidence: 99%
“…This avoids the use of arbitrary a priori thresholds (e.g., ±10% or ±20%) that produce dichotomous outcomes that are sensitive to minor deviations in threshold selection ( 14 ). Specifically, a review on the topic demonstrated that a 5% change in threshold selection altered the conclusions of 75% and 71% of validation studies in children/youth and adults, respectively ( 14 ). In the absence of clinically acceptable equivalence zones, we also recommend that researchers consider reporting the zone required for the measures to be deemed equivalent as a percentage and/or as a proportion of the SD (e.g., 0.5 SD).…”
Section: How To Interpret Validation Study Results?mentioning
confidence: 99%
See 1 more Smart Citation
“…The ±10% equivalence zone of the reference mean was selected based on previous validation studies of physical behaviours measures. However, as presented by O'Brien (2021), the selection of an equivalence zone (i.e., narrow versus broad) influences equivalence test outcomes. Therefore, as there is no evidence of a standardised equivalence criteria, this study also reported a minimum equivalence zone for the PSG estimates that include 90% CI of the accelerometer sleep estimates.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the use of a 10% zone can be strict when values are highly variable and smaller but lax when values are very high and across a narrow range of values [ 29 ]. Therefore, the absolute equivalence zone needed to reach equivalence is provided alongside the relative equivalence zone presented as a proportion of the SD [ 30 ]. To aid interpretations, a strict threshold of 3%, indicative of excellent agreement between algorithms, was used to aid interpretations of the absolute equivalence zone [ 26 ].…”
Section: Methodsmentioning
confidence: 99%